PENAMBAHAN PUREE LABU KUNING (Cucurbita moschatta duch) DALAM PEMBUATAN SERABI BERAS MERAH (Oryza nivara) - Putri, Devina Aulia; Fadhilah, Tri Marta (UHAMKA PRESS, 2023)
Vitamin A is the most important nutrient. One of the efforts to help overcome the problem of vitamin A deficiency (VAD) in the community that can be done is to develop local food products or snacks. The development of snacks that can be done is making serabi innovation. Serabi is a traditional market snack originating from Indonesia. This study aims to analyze organoleptic, acceptability, β-carotene levels and SNI quality (water content, ash content, fat content and sugar content) in red rice serabi products with the addition of pumpkin puree. Quantitative research method called experimental research design, with the dependent variable is physical, chemical, organoleptic, and hedonic properties and the independent variable is the variation of serabi formulation consisting of F1 = 50g; F2 = 40g; F3 = 30g for brown rice flour, F1 = 50g; F2 = 60g; F3 = 70g for pumpkin puree. Statistical test results for organoleptic tests showed significant differences (p-value <0.05) in color indicators. The highest hedonic test results were in formula F3 with a total percentage of 88.82% (very like). The test results of β-Carotene content were highest in F3 at 88.78 mg, highest water content in F2 at 44.30%, highest ash content in F1 at 2.84%, highest fat content in F3 at 14.42%, highest sugar content in F3 at 14.32%. This research shows that red rice serabi with the addition of pumpkin puree can be accepted by the public.